Construction of low Cost houses - Ali Hussein khudhair; Haydair Abbas Bdewi; Ameen Sadki Abduallah (Journal of Madenat Alelem University College, 2017)
This research deals with the construction of a low cost house from available local materials with high permanency and good resistance to the atmospheric circumstance. The research begins with collecting informations about the construction materials locally available; to select the less cost materials having good resistance and the less cost methods of construction. The decision is made to construct a house from normal bricks in arc shaped roof with a crown height not exceed (10-25) cm. and spans up to (5meters), without use of steel section or steel reinforcement. This construction saves the cost of (reinforcement, concrete, works of concrete placing and forms). This construction can be used for multi stories purposes. The use of bricks for roofing provides better insulation than concrete roof, which will reduce the cost of air conditioning. Collecting the informations, the necessary design is made to find minimum curvature which will achive the safe construction requirements for the house. Fifteenth experimental models for studying (maximum curve high, type of motar material and span width) had been done. Testing on site of these models have been made to prove the idea. Research results indicated that crown height of (15 – 25 ) cm. at (4) m. span yield the best results .